Management Effectiveness Based on High School in North Mollo District (Studies at Kapan State High School and Kapan Christian High School) - BOIMAU, Yerfiana Akas Demarci; DJAHA, Ajis Salim Adang; NEOLAKA, Melkiesedek. N. B. C. Neolaka (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose:Through the School-Based Management (MBS) system, each school seeks to attract consumers (students) to make choices about their school, so the author wants to find out what and how School-Based Management in Kapan State High School and Kapan Christian High School influences school competition in getting new students or other factors.Methodology:The method used in this research is a descriptive method with a qualitative approach with 76 people who were determined purposively. Then, the primary and secondary data collected were analyzed using data analysis techniquesFindings:The results of the research found that the implementation of School-Based Management in Kapan State High School, Kapan Christian High School, was the most effective in its implementation based on the classification by the author according to the level of classification of effective, less effective, and ineffective.Implication:The research showed that Kapan Christian High School was the most effective in implementing Based Management. School (MBS) is the least effective, followed by Kapan State High School.